Electron linacs in NSC KIPT: R&D and application - Antipov, K.I.; Ayzatsky, M.I.; Akchurin, Yu.I.; Boriskin, V.N.; Beloglasov, V.I.; Biller, E.Z.; Demidov, N.V.; Dikiy, N.P.; Dovbnya, A.N.; Dovbush, L.S.; Gurin, V.A.; Karasyov, S.P.; et al. (Вопросы атомной науки и техники, 2001)
A review is given about electron linacs of NSC KIPT and their some applications for research of radiation effects in reactor materials, channeling, plasma-beam interactions, geology (gamma-activation analysis of ore samples), as well as sterilization of single-use medical products, modification of polymers and semiconductors, isotope production for nuclear medicine etc.